«A hand for sword – a heart for Lady»: the interpretation of love in the North French knightly romance - Mojeiko, Marina A. (Journal of the Belarusian State University. Sociology, 2019)
The article is devoted to the analysis of the preconditions for the formation of a hypothetical model of love in a knightly medieval culture. The axiological shifts in the development of Middle Ages culture, that led to the transformation of the knightly culture in the direction of secular form, are revealed.